Preparation of α- MnO2 Nanowires Coated with Hybrid of Manganese and Cerium Oxides and Studying Their Catalytic Performance Toward Electro-Oxidation of L- Methionine. Issue 1 (1st January 2023) - Rashedi, Maryam; Alizadeh, Taher
Abstract : A facile synthetic method for mixed transition metal oxide, with a desirable potential for electrochemical determination of L-methionine, was proposed. The hierarchical nanostructure, MnO2 @MnCeO, was prepared by a hydrothermal process followed by calcination at 350 °C. The structure has a backbone made of α - MnO2 nanowires covered with a hybrid of manganese and cerium oxides. The crystallographic analysis demonstrated that the phases of MnO2 formed on the backbone surface and the backbone MnO2 are the same. The synthesized material was employed for the modification of a carbon paste electrode to design an outstanding sensor for L-methionine determination. The electrocatalytic activity of α -MnO2 nanowires covered by mixed oxides of MnCeO and single oxide of CeO toward L-methionine electrooxidation were compared to each other. It was revealed that the MnO2 @MnCeO modified carbon paste elecrode exhibited better analytical performance than the one modified with MnO2 @CeO. This composite electrode was successfully applied in L-methionine assessments in two ranges of concentration, 1000–10000 and 1–750 μ mol l −1 with a detection limit as low as 0.16 μ mol l −1 . Owing to the remarkable sensitivity and promising selectivity of the prepared electrode, it could assess methionine content in complex matrices of human plasma samples.